«MENTAL CON TEMPLATION» OF IVAN S. TOURGENEV, THINKER AND ARTIST - Vyacheslav M. Golovko (Вестник Северо-Кавказского федерального университета, 2022)
I. S. Tourgenev's ontological paradigm is analyzed in the process of identification of outlook constants that organize the philosopically thinking writer's aesthetic space. The existent and the being, active and contemplative attitude towards the world, nature and essence of a human, oppositions between the natural and the moral, personal and social aspects of life within the ontology of humanity's being are elucidated from the point of view of imminent conflict-related organization of I. S. Tourgenev's world picture, of the "development idea" which constitutes the stronger part of the great writer's outlook.